“Determinantes socioeconómicos y demográficas del acceso a crédito de los hogares del cantón Saraguro provincia de Loja 2023” - Garcia Silva, Luis Eduardo (2023)
In Ecuador, at least one third of the population has access to credit. And 54% is concentrated among people with an average income of 1,200 dollars, while only 7 out of every 100 loans are granted to people with an income of less than 300 dollars. The general objective of this research is to analyze the main socioeconomic and demographic determinants of access to financial credit for households in the canton of Saraguro, province of Loja, through the application of surveys and the use of descriptive statistics using the simple OLS regression model in order to have available information as an input for decision-making on financial inclusion in the locality. The results found in the research in relation to the most relevant demographic determinants for accessing credit in Saraguro canton are age and occupation of credit applicants, as well as the most significant socioeconomic determinants are the type of housing owned, employment, the remuneration received, and the destination of the credit requested. Finally, it is recommended that sound financial regulation policies be established with the collaboration of various actors, including the government, financial institutions and oversight organizations to create a safe and reliable environment for financial inclusion.